The effect of scientific evidence on conservation practitioners' management decisions - Walsh, Jessica C.; Dicks, Lynn V.; Sutherland, William J. (Conservation biology, 2015)
A major justification of environmental management research is that it helps practitioners, yet previous studies show it is rarely used to inform their decisions. We tested whether conservation practitioners focusing on bird management were willing to use a synopsis of relevant scientific literature to inform their management decisions. This allowed us to examine whether the limited use of scientific information in management is due to a lack of access to the scientific literature or whether it is because practitioners are either not interested or unable to incorporate the research into their decisions. In on-line surveys, we asked 92 conservation managers, predominantly from Australia, New Zealand, and the United Kingdom, to provide opinions on 28 management techniques that could be applied to reduce predation on birds. We asked their opinions before and after giving them a summary of the literature about the interventions' effectiveness. We scored the overall effectiveness and certainty of evidence for each intervention through an expert elicitation process—the Delphi method. We used the effectiveness scores to assess the practitioners' level of understanding and awareness of the literature. On average, each survey participant changed their likelihood of using 45.7% of the interventions after reading the synopsis of the evidence. They were more likely to implement effective interventions and avoid ineffective actions, suggesting that their intended future management strategies may be more successful than current practice. More experienced practitioners were less likely to change their management practices than those with less experience, even though they were not more aware of the existing scientific information than less experienced practitioners. The practitioners' willingness to change their management choices when provided with summarized scientific evidence suggests that improved accessibility to scientific information would benefit conservation management outcomes. Una justificación mayor de la investigación en el manejo ambiental es que ayuda a quienes lo practican, aunque estudios previos muestran que rara vez se usa para informar sus decisiones. Probamos si quienes practican la conservación enfocada en el manejo de aves estaban dispuestos a usar una sinopsis de literatura científica relevante para informar sus decisiones de manejo. Esto permitió que examináramos si el uso limitado de información científica en el manejo se debe a una falta de acceso a la literatura científica o si se debe a que quienes practican la conservación no están interesados o no son capaces de incorporar la investigación a sus decisiones. En encuestas en línea les preguntamos a 92 practicantes de la conservación, la mayoría de Australia, Nueva Zelanda y el Reino Unido, que nos proporcionaran opiniones sobre 28 técnicas de manejo que podrían aplicarse para reducir la depredación de aves. Les pedimos sus opiniones antes y después de darles un resumen de la literatura sobre la efectividad de las intervenciones. Calificamos la efectividad general y la certidumbre de la evidencia para cada intervención por medio de un proceso de extracción por expertos - el método Delphi. Usamos las calificaciones de la efectividad para evaluar el nivel de entendimiento y de precatación de la literatura de quienes practican la conservación. En promedio, cada participante de la encuesta cambió su probabilidad de usar 45.7% de las intervenciones después de leer la sinopsis de la evidencia. Fue más probable que implementaran intervenciones efectivas y evitar acciones poco efectivas, lo que sugiere que sus estrategias de manejo futuras puedan ser más exitosas que las de práctica actual. Los practicantes con mayor experiencia tuvieron una menor probabilidad de cambiar sus prácticas de manejo que aquellos con menos experiencia, aunque no estuvieron más conscientes de la información científica existente que quienses tenían menos experiencia. La disponibilidad de los practicantes para cambiar sus opciones de manejo al proporcionárseles evidencia científica resumida sugiere que el acceso mejorado a la información científica podría beneficiar los resultados del manejo de la conservación.